Constrained feedback RMPC for LPV systems with bounded rates of parameter variations and measurement errors. (2012) - Zheng, Pengyuan; Li, Dewei; Xi, Yugeng
For Linear Parameter Varying (LPV) systems with bounded rates of parameter variations and bounded parameter measurement errors, a feedback Robust Model Predictive Control (RMPC) is designed by utilising the information on system parameters. A sequence of feedback control laws is designed based on the model with parameter-incremental uncertainty. Since the sequence of feedback control laws corresponds to the future variations of system parameters and introduces additional freedom, the control performance of RMPC can be improved. The recursive feasibility and closed-loop stability of the proposed RMPC are also proven.